Soil Modeling and Soil Moisture Changes Depending on the Level of Groundwater - Isaev Sabirjan Khusanbayevich; Ashirov Yusufboy Rakhimberganovich; Bazarbayeva Bahadir Abatbay ugli (Researchparks Publishing, 2022)
This article provides information on the creation of a mathematical model by analyzing data on changes in the soil layer and soil moisture depending on changes in the level of seeping water.